STUDY KEGAGALAN AKIBAT KOROSI PADA PIPA ECONOMIZER - Acep Wagiman; Gugun Gundara (Universitas Muhammadiyah Metro, 2017)
Failure analysis to the economizer tube of boiler with operation pressure ± 190 bar, in holding time 6 hour gacor slot have been investigated. The economizer tube is carbon steel, ASTM A210 Grade C, outside diameter ± 51 mm and thickness ± 6 mm. The investigation cause of failure from the economizer tube included : chemical composition and metallography analysis, visual examination at outer and inner fire side, measuring thickness and densities of the scale at inner fire side and wall side, chemical composition analysis of the at surface crust the economizer tube. From the results of visual investigation to both outer and inner fire side of the economizer tube shown that at fire side occur decrease thickness gacor slot of the wall tube, with minimum thickness are 1.37 mm and 2,50 mm, respectively. Those caused by erosion corrosion result from effect the fly ash. Beside that, at inner fire side of the gacor slot economizer tube occur light pitting corrosion result by oxygen corrosion.Keywords : Economizer tube, boiler, fire side, fly ash, erosion corrosion, pitting corrosion, scale, oxygen